The Effect of Organic and Biological Fertilizers on the Movement of Heavy Metals (Cu, Zn) in the Soil-Plant System - Raimovich, Boynazarov Baxron; Ismailovna, Djumaniyazova Gulnara; Usmonovich, Eshboboyev Turakul (American Journal of Botany and Bioengineering, 2024)
The article experimentally proves that the use of Teria-S bacterial fertilizer, K-Gumat organic fertilizer, and Serhosil biopreparation during the cultivation of wheat plants in soil conditions contaminated with industrial waste belonging to the Almalyk Mining and Metallurgical Combine (Joint Stock Company) reduced the amount of heavy metals (Cu, Zn) in the organs of the grown wheat plants.